Early Delays in Insurance Coverage and Long-term Use of Home-based Peritoneal Dialysis. Issue 7 (July 2020) - Lin, Eugene; Chertow, Glenn M.; Bhattacharya, Jay; Lakdawalla, Darius
Abstract : Background: Uninsured patients with end-stage renal disease face barriers to peritoneal dialysis (PD), a type of home dialysis that is associated with improved quality of life and reduced Medicare costs. Although uninsured patients using PD at dialysis start receive retroactive Medicare coverage for required predialysis services, coverage only applies for the calendar month of dialysis start. Thus, initiating dialysis later in the month yields longer retroactive coverage. Objectives: To examine whether differences in retroactive Medicare were associated with decreased long-term PD use. Research Design: We exploited the dialysis start date using a regression discontinuity design on a national cohort from the US Renal Data System. Subjects: 36, 256 uninsured adults starting dialysis between January 1, 2006 and December 31, 2014. Measures: PD use at dialysis days 1, 90, 180, and 360. Results: Starting dialysis on the first versus last day of the calendar month was associated with an absolute decrease in PD use of 2.7% [95% confidence interval (CI), 1.5%–3.9%], or a relative decrease of 20% (95% CI, 12%–27%) at dialysis day 360. The absolute decrease was 5.5% (95% CI, 3.5%–7.2%) after Medicare established provider incentives for PD in 2011 and 7.2% (95% CI, 2.5%–11.9%) after Medicaid expansion in 2014. Patients were unlikely to switch from hemodialysis to PD after the first month of dialysis (probability of 6.9% in month 1, 1.5% in month 2, and 0.9% in month 4). Conclusions: Extending retroactive coverage for preparatory dialysis services could increase PD use and reduce overall Medicare spending in the uninsured. Abstract : Supplemental Digital Content is available in the text.